Canadian Weathercasters' Current and Potential Role as Climate Change Communicators. Issue 6 (18th August 2019) - McIlroy-Young, Bronwyn; Thistlethwaite, Jason
ABSTRACT: Climatologists worldwide are calling for urgent action to manage climate change, but public engagement remains a significant challenge. This lack of engagement is often attributed to psychological distance: climate change is perceived as something happening far away, to other people, or in a hypothetical future. TV weathercasters are ideally situated to communicate the geographically and temporally proximate impacts of climate change and increase public engagement. This study explores the status of climate change reporting amongst weathercasters in Canada, where no such research has been conducted. The respondents suggested that many, but not all, weathercasters are engaged with climate change and interested in presenting local, climate-related content; however, their on-air climate change communication behavior is highly limited. This analysis builds on research conducted with American weather broadcaster by indicating that Canadian weathercasters share their potential as effective climate change communicators, but are highly uncertain about their capacity to support this role.